Overview of Professional Dental Students' Knowledge of Patient Safety Goals at Universitas Muhammadiyah Semarang Oral and Dental Hospital, Indonesia - Annisa Maharani; Retno Kusniati; Nur Khamilatusy Sholekhah; Trixie Salawati (Indonesian Journal of Medicine, 2026)
Background: Patient safety refers to actions taken to prevent medical errors and adverse events related to healthcare services, particularly in hospitals where the risk of patient safety incidents is relatively high. Professional dental students are involved in planning and performing patient care under the supervision of the attending physician, making it important to assess their level of knowledge regarding patient safety goals, which may influence the quality of hospital services. This study aimed to assess the knowledge of dental professional students regarding the six dimensions of patient safety goals established by the World Health Organization. Subjects and Method: This study was conducted in December 2025 and involved 104 professional dental students who were actively participating in the Integrated Clinic at Universitas Muhammadiyah Semarang Dental Hospital, Semarang, Indonesia. A quantitative study with a cross-sectional design was employed. Data were collected using printed questionnaires that were distributed and collected on the same day. The variable examined was the level of knowledge of professional dental students regarding patient safety goals. Descriptive statistical analysis was used to present the characteristics of the respondents. Results: Among 104 professional dental students, the overall knowledge regarding patient safety goals was categorized as good (mean score=80.93%). The highest knowledge score is Improve Effective Communication dimension (96.8%), whereas the lowest score was found in the Identify Patient Correctly dimension (64.73%). Conclusion: The knowledge of professional dental students regarding patient safety goals at Universitas Muhammadiyah Semarang Dental Hospital is categorized as good.